Las decisiones inconstitucionales del Tribunal Constitucional - Castillo Córdova, Luis (2015)
Can the decisions of a Constitutional Court or Supreme Court be unconstitutional? The answers found in the doctrine and even on constitutionalcase law are not uniform, becoming this question a controversial theme, although   extremely important for Constitutional Law.In this article, the author, considering that the Constitutional Court is the supreme interpreter and controller of the Constitution and, as such, creates Constitutional Law, maintains that the decisions which the Constitutional Court takes can be unconstitutional. Focusing on the Peruvian legal system, the author also presents alternatives to solve the problem these unconstitutional decisions cause.